The Effect of Students' Self-Efficacy on Students' Mathematical Communication Skills in Elementary School - Winggowati, Sri; Wahyudin; Herman, Tatang; Fauzi, Irfan (UNNES JOURNAL, 2025)
The low mathematical ability of students is a major challenge that needs to be addressed in elementary school mathematics education. The goal of this study is to assess the impact of students' self-efficacy on their mathematical communication skills. The method in this study uses a quantitative approach with comparative causal types using correlation and regression analysis. The population in this study is fifth-grade students in Bandung, and the sample used is 84 fifth-grade students from one of the elementary schools in Bandung. The instruments used in this study were students' mathematical communication skills test questions, totaling 4 questions with the type of story questions on comparative material, and non-test instruments in the form of questionnaires related to students' self-efficacy. Data analysis in this study used SPSS 24 software to analyse the correlation and regression of students' self-efficacy and their mathematical communication skills. Additionally, a qualitative descriptive analysis was conducted on the students' responses regarding their mathematical communication skills. The research results indicate that, 1) there is a positive correlation between students' self-efficacy and their mathematical communication abilities with the correlation coefficient R = 0.219, which means that 4.8% of students' mathematical communication skills are determined by self-efficacy factors, 2) Students' self-efficacy has a positive effect on their mathematical communication skills with the regression equation y = 57.8 + 0.6x, which means that every time self-efficacy scores increase by 10 units, students' mathematical communication skills scores increase by 6 units. This research serves as a basis in the effort to create effective and meaningful mathematics learning by considering mathematical communication and students' self-efficacy. Abstrak Rendahnya kemmapuan matematis siswa menjadi tantang besar yang harus dikembangkan dalam pendidikan matematika sekolah dasar. Tujuan penelitian ini adalah untuk menilai dampak efikasi diri siswa terhadap kemampuan komunikasi matematis. Metode dalam penelitian ini menggunakan pendekatan kuantitatif dengan tipe kausal komparatif dengan menggunakan analisis korelasi dan regresi. Populasi pada penelitian ini adalah siswa kelas 5 di Bandung, dan sampel yang digunakannya adalah 84 siswa kelas 5 di salah satu sekolah dasar negeri di Bandung. Instrumen yang digunakan pada penelitian ini adalah soal tes keterampilan komunikasi matematis siswa, berjumlah 4 soal dengan jenis soal cerita pada materi perbandingan, dan instrumen non tes berupa kuesioner terkait self-efficacy siswa. Analisis data dalam penelitian ini menggunakan softwere SPSS 24 untuk menganalisis korelasi dan regresi efikasi diri siswa dan keterampilan komunikasi matematisnya. Selain itu, dilakukan analisis hasil jawaban siswa berkaitan dengan komunikasi matematias. Hasil penelitian menunjukkan bahwa, 1) terdapat korelasi positif antara efikasi diri siswa dengan kemampuan komunikasi matematisnya dengan koefisien korelasi R = 0.219, yang berarti bahwa 4.8% kemampuan komunikasi matematis siswa ditentukan oleh faktor efikasi diri, dan 2) efikasi diri siswa berpengaruh positif pada kemampuan komunikasi matematisnya dengan persamaan regresi y = 57.8 + 0.6x, yang berarti setiap kali skor efikasi diri meningkat 10 unit, skor keterampilan komunikasi matematis siswa meningkat 6 unit. Penelitian ini menjadi dasar dalam upaya menciptakan pembelajaran matematika yang efektif dan bermakna dengan memperhatikan komunikasi matematis dan self-efficacy siswa